The Implementation of Smart Indonesia Program Policy: A Case Study in Banyumas - Ela Fatimah (JURNAL KUASA, 2025)
This study aims to identify and examine the implementation of the Smart Indonesia Program (Program Indonesia Pintar – PIP) policy at SD Negeri 2 Sokaraja Tengah for the 2024/2025 academic year using George C. Edward III's policy implementation model. The method used is descriptive qualitative. The results of the study indicate that the success of PIP policy implementation is influenced by four main factors: communication, resources, disposition, and organizational structure. In terms of communication, although there is clear information exchange between the school and students’ parents, the transmission of information between the government and the school remains suboptimal, particularly concerning follow-up socialization and procedural changes. Overall, while the implementation of the PIP policy at the school level has been fairly effective, there is still a need to improve communication among stakeholders and ensure equitable fund allocation so that the impact of the policy can be more widely felt by its beneficiaries.